2021
DOI: 10.1016/j.cjco.2021.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Transcarotid Transcatheter Aortic Valve Replacement in an Octogenarian With Complex Type B Aortic Dissection and Aneurysm: A Case Report

Abstract: We report the case of an octogenarian with severe aortic valve stenosis, chronic kidney disease (CKD) and heart failure. Due to advanced CKD, we used a 3-dimensional transesophageal echocardiogram for sizing the device before transcatheter aortic valve replacement (TAVR). Noncontrast computed tomography found complex aortic dissection involving the arch, descending thoracic aorta, and abdominal aorta. TAVR was approached via the right carotid artery using a CoreValve. There was no cerebral vascular event. Rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…An overview of the studies is provided in Table 1 (Ref. [ 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]). Most of these studies had a moderate risk of bias in accordance with the Newcastle-Ottawa Scale, as shown in Supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An overview of the studies is provided in Table 1 (Ref. [ 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]). Most of these studies had a moderate risk of bias in accordance with the Newcastle-Ottawa Scale, as shown in Supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Different types of transcatheter heart valves were used as cited by the twenty studies (Table 2b , Ref. [ 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]). Most of these studies used SAPIEN and CoreValve which are largely imported from western countries, while a minority used heart valves produced in Asia like the J-Valve and LOTUS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations